Aversive cues fail to activate fos expression in the asymmetric olfactory-habenula pathway of zebrafish - Decarvalho, Tagide N.; Akitake, Courtney M.; Thisse, Christine; Thisse, Bernard; Halpern, Marnie E. (Frontiers in Neural Circuits, 2013)
The dorsal habenular nuclei of the zebrafish epithalamus have become a valuable model for studying the development of left-right (L-R) asymmetry and its function in the vertebrate brain. The bilaterally paired dorsal habenulae exhibit striking differences in size, neuroanatomical organization and molecular properties. They also display differences in their efferent connections with the interpeduncular nucleus (IPN) and in their afferent input, with a subset of mitral cells distributed on both sides of the olfactory bulb innervating only the right habenula. Previous studies have implicated the dorsal habenulae in modulating fear/anxiety responses in juvenile and adult zebrafish. It has been suggested that the asymmetric olfactory-habenula pathway (OB-Ha), revealed by selective labeling from an lhx2a:YFP transgene, mediates fear behaviors elicited by alarm pheromone. Here we show that expression of the fam84b gene demarcates a unique region of the right habenula that is the site of innervation by lhx2a:YFP-labeled olfactory axons. Upon ablation of the parapineal, which normally promotes left habenular identity; the fam84b domain is present in both dorsal habenulae and lhx2a:YFP-labeled olfactory bulb neurons form synapses on the left and the right side. To explore the relevance of the asymmetric olfactory projection and how it might influence habenular function, we tested activation of this pathway using odorants known to evoke behaviors. We find that alarm substance or other aversive odors, and attractive cues, activate fos expression in subsets of cells in the olfactory bulb but not in the lhx2a:YFP expressing population. Moreover, neither alarm pheromone nor chondroitin sulfate elicited fos activation in the dorsal habenulae. The results indicate that L-R asymmetry of the epithalamus sets the directionality of olfactory innervation, however, the lhx2a:YFP olfactory-habenula pathway does not appear to mediate fear responses to aversive odorants.